VizieR Online Data Catalog: Variable AGN candidates catalog (Pouliasis+, 2019) - Pouliasis, E.; Georgantopoulos, I; Bonanos, A. Z.; Yang, M.; Sokolovsky, K. V.; Hatzidimitriou, D.; Mountrichas, G.; Gavras, P.; Charmandaris, V; Bellas-Velidis, I.; Spetsieri, Z. T.; Tsinganos, K. (VizieR Online Data Catalog, 2020)
Based on observations made with the NASA/ESA Hubble Space Telescope, and obtained from the Hubble Legacy Archive, which is a collaboration between the Space Telescope Science Institute (STScI/NASA), the Space Telescope European Coordinating Facility (ST-ECF/ESA) and the Canadian Astronomy Data Centre (CADC/NRC/CSA). (1 data file).
Keywords: Active gal. nuclei; Magnitudes; Redshifts; X-ray sources